Liver-specific deletion of the Plpp3 gene alters plasma lipid composition and worsens atherosclerosis in apoE(-/-) mice - Busnelli M; Manzini S; Hilvo M; Parolini C; Ganzetti GS; Dellera F; Ekroos K; Jänis M; Escalante-Alcalde D; Sirtori CR; Laaksonen R; Chiesa G (NATURE PUBLISHING GROUP, 2022)
The PLPP3 gene encodes for a ubiquitous enzyme that dephosphorylates several lipid substrates. Genome-wide association studies identified PLPP3 as a gene that plays a role in coronary artery disease susceptibility. The aim of the study was to investigate the effect of Plpp3 deletion on atherosclerosis development in mice. Because the constitutive deletion of Plpp3 in mice is lethal, conditional Plpp3 hepatocyte-specific null mice were generated by crossing floxed Plpp3 mice with animals expressing Cre recombinase under control of the albumin promoter. The mice were crossed onto the athero-prone apoE(-/-) background to obtain Plpp3(f/f)apoE(-/-) Alb-Cre(+) and Plpp3(f/f)apoE(-/-) Alb-Cre(-) offspring, the latter of which were used as controls. The mice were fed chow or a Western diet for 32 or 12 weeks, respectively. On the Western diet, Alb-Cre+ mice developed more atherosclerosis than Alb-Cre- mice, both at the aortic sinus and aorta. Lipidomic analysis showed that hepatic Plpp3 deletion significantly modified the levels of several plasma lipids involved in atherosclerosis, including lactosylceramides, lysophosphatidic acids, and lysophosphatidylinositols. In conclusion, Plpp3 ablation in mice worsened atherosclerosis development. Lipidomic analysis suggested that the hepatic Plpp3 deletion may promote atherosclerosis by increasing plasma levels of several low-abundant pro-atherogenic lipids, thus providing a molecular basis for the observed results.